Professional Rules for Attorneys as a Subject of Legal Education in Germany - Kirchner, Stefan (University of Wroclaw. Faculty of Law, Administration & Economics, 2014)
The German system of lawyer training has been subjected to many reforms but has kept its central structure for centuries. This structure consists of theoretical training in universities, followed by the first state examination in law, two years of practical experience and the second state examination in law. While the overwhelming majority of law school graduates enters professional practice as attorneys, the structure of the training of legal professionals in Germany still aims at producing legal scholars who are qualified to eventually work as judges. Indeed, passing the second state examination in law is not only a prerequisite for becoming an attorney but also qualifies one to work as a judge. This gap between academic training and practical reality raises the question how young lawyers are trained with regard to the rules which govern the exercise of the profession of an attorney. This text approaches the issue from the perspective of a university lecturer who is also a practicing attorney admitted to the bar in Germany and who has been responsible for training young lawyers during their two year Referendariat. In doing so, the text includes an overview over the education provided both at university and in practice. Because the contents of lawyer training vary between the sixteen federal states of the Federal Republic of Germany, this analysis uses also a comparative law approach to provide a better understanding of the different role this issue plays in different German states. It is shown that there is a substantial range of different approaches. While there are already some tendencies towards more practical legal training already at the university level, it will be shown that there is still some room for improvement.
Keywords: Niemcy; edukacja prawnicza; adwokat